Clinical decision‐making in complex endodontic cases between postgraduate students across dental specialties at a UK dental school: A pilot study. (2nd January 2022) - Liew, Jonathan; Zainal Abidin, Imran; Cook, Neil; Kanagasingam, Shalini
Abstract: Introduction: Treatment decisions for a heavily restored endodontically treated tooth vary amongst clinicians owing to multitude of factors. This phenomenon not only often poses dilemmas to clinicians of different clinical backgrounds, but also exerts a degree of treatment difficulty to the treating clinician. Previous studies indicated that specialty training and clinical experience significantly impacted clinical decision‐making process. Materials and methods: Master of Science postgraduate students in endodontics, prosthodontics, periodontics, oral surgery and implantology participated in a questionnaire‐based cross‐sectional study. The dental specialties were further categorised into restorative and surgical dentistry. A multiple‐choice questionnaire with three clinical cases was distributed to the students. Data were analysed for trends using descriptive statistics. Results: There was a 44% response rate; the majority of respondents were from restorative dentistry specialties. Cases 1 and 2 were rated as moderate to high difficulty, and Case 3 was predominantly rated as high difficulty with procedure predictability being the main factor affecting their clinical decision‐making in three cases. Endodontic retreatment was selected as the preferred treatment in Cases 1 and 2 and periradicular surgery in Case 3. The students were fairly confident in managing Cases 1 and 2, but not in Case 3. Referral patterns were consistent in Cases 1 and 2 with endodontists being the first choice of referral except for Case 3 where 48% preferred to refer to oral surgeons and 35% choosing endodontists. Some indication of differences between specialties were noted throughout. Years in practice appeared to be related to the importance of predictability in Case 3 only. Conclusion: Considerable inter‐clinician variability was noted whereby specialty postgraduate training impacted on clinical decision‐making. Overall, procedural predictability, technical difficulty, risk of damage to the tooth and patient preference were the most highly ranked factors affecting clinical decision‐making. Evidence‐based treatment guidelines and dental curricula should be reviewed to enhance inter‐clinician agreement in clinical decision‐making, ultimately improving patient care.